Mental Distress, Perceived Stress, and Resilience among Special Students During Covid-19 Pandemic - Sheeza Khalil, Asadullah Khan, Iffat Batool, Muhammad Zohaib Khan, Shah Rukh Tariq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Almost everyone in society has been affected by the Covid epidemic.However, it has a different impact on individuals who have disabilities or special needs. Aim: To explore the relationship between mental distress, perceived stress, and resilience among special students during the Covid pandemic. Method:Cross-sectional correlational research design was used to investigate the relationship between study variables. The total sample of n=250 special students consisted of 100(40%) females and 150(60%) with having age range from 15 to 30 years. The purposive sampling technique was employed to collect the data by using different research instruments (e.g.,Patient Health Questionnaire, Perceived Stress Scale, and Final Resilience Scale). Results: Results were drawn using correlation and multiple regression analyses. To explore gender differences, an independent t-test was computed. It was concluded that mental distress is negatively correlated with resilience and positively correlated with perceived stress. Pracctical Implication: This research would be helpfulfor the teachers of the special education centers, they train their how they develop resilience hence they may become emotionally stable and deal effectively with any worrisome circumstance well. It will help school administration of the special students’to conduct workshops on the resilience so that students could deal with their mental distress and perceived stress effectively. Conclusion: There was little published research on the variables examined in this study, particularly in Pakistan. To increase the body of knowledge, research on this subject must be done in Pakistan. Keywords: Mental distress, Resilience, Perceived stress, Special students, CovidPendemic.